Internal medicine - Brochert, Adam (Hanley & Belfus, 2002)
(Hanley & Belfus) Medical College of Georgia, Savannah. Presents 50 case scenarios to give the reader clear advantage on the vignette-based Step 2 exam. Buzzwords are highlighted, and 'More High-Yield Facts' are included. Softcover.